The Effectiveness of Using Learning Models P-O-E (Predict, Observe, Explain) Against Science Process Skills for Class VIII Junior High School Students - Eka Sri Rahmawati (International Consortium of Education and Culture Research Studies, 2020)
This study aims to identify the effectiveness of the use of POE learning model to the science process skill of grade VIII SMP students. The research design used in this research is pre experiment with one group pretest posttest design. Sampling was done using a random cluster sampling technique. In this research is also used descriptive method that describes the results of the study. The research instrument used is a test of science process skill in essay form. Prior to the question of science process skill used on the students, the content validation and construct validation were first done, and 16 science test of science process skills were obtained. Student learning outcomes after being given learning by using the model of learning POE in class VIII in SMPN 1 Tarik the results of the achievement of science process skills increased and it can be concluded that the use of effective learning model of POE to the skills of science process students of grade VIII SMP.